2008
DOI: 10.1016/j.lungcan.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Frequent p16 inactivation by homozygous deletion or methylation is associated with a poor prognosis in Japanese patients with pleural mesothelioma

Abstract: This study examined the p16 expression status and the P16 gene deletion and methylation status in specimens from Japanese patients with malignant pleural mesothelioma (MPM). Immunohistochemical staining for p16 protein and fluorescence in situ hybridization for the P16 gene were performed using specimens from 30 Japanese patients with primary MPM. The methylation status of the P16 gene was examined in 13 patients whose frozen tumor specimens were available using a methylation-specific PCR assay. Among the 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
(29 reference statements)
2
38
0
Order By: Relevance
“…Similar to our findings, a recent study of pleural mesotheliomas showed that all 21 cases with CDKN2A deletion had loss of p16 expression by IHC, and that two of the three cases with p16 loss without deletion showed CDKN2A gene methylation. 25 This and other studies have shown that, at least in a small percentage of pleural mesotheliomas (11-21%), the CDKN2A gene is inactivated by methylation. [24][25][26] Although we did not test for aberrant methylation of the CDKN2A gene, a similar percentage of our peritoneal mesothelioma cases (19%) showed loss of p16 expression without loss of the CDKN2A gene.…”
Section: Am Krasinskas Et Almentioning
confidence: 70%
See 1 more Smart Citation
“…Similar to our findings, a recent study of pleural mesotheliomas showed that all 21 cases with CDKN2A deletion had loss of p16 expression by IHC, and that two of the three cases with p16 loss without deletion showed CDKN2A gene methylation. 25 This and other studies have shown that, at least in a small percentage of pleural mesotheliomas (11-21%), the CDKN2A gene is inactivated by methylation. [24][25][26] Although we did not test for aberrant methylation of the CDKN2A gene, a similar percentage of our peritoneal mesothelioma cases (19%) showed loss of p16 expression without loss of the CDKN2A gene.…”
Section: Am Krasinskas Et Almentioning
confidence: 70%
“…23 In pleural mesotheliomas, loss of p16 protein expression is typically associated with CDKN2A deletion, but a subset of cases showed loss of p16 due to inactivation of the gene by methylation. [24][25][26] The correlation between CDKN2A deletion, loss of p16 protein expression and survival has not been made in peritoneal mesotheliomas.…”
mentioning
confidence: 99%
“…[21][22][23] In addition, homozygous CDKN2A deletions are a poor prognostic indicator for patients with pleural mesothelioma. 22,24,25 NF2, located on chromosome 22q12, is mutated in 50% of pleural mesotheliomas with corresponding loss of the wild-type allele by deletion of either 22q or all of chromosome 22. 16,26 Hemizygous loss of NF2 is associated with increased mesothelioma proliferation, invasiveness, spreading, and migration.…”
mentioning
confidence: 99%
“…Among the examined molecules, the P16 INK4a gene, which is located at chromosome 9p21, is frequently deleted in MPM, and it has been demonstrated that its deletion results in the dysregulation of cell-cycle control through the Rb pathway and malignant transformation (18,19). In addition, the present authors have previously reported that DNA methylation of P16 is another mechanism that leads to the loss of p16 expression (7). In the present study, P16 deletion was observed in YUMC44 and YUMC64 cells, and P16 was methylated completely in YUMC8, YUMC44, and YUMC64 cells and partially in YUMC63 cells.…”
mentioning
confidence: 71%
“…In the current study, 4 MPM cell lines were established from Japanese patients and the methylation status, presence of mutations, copy number and protein expression of representative genes, including NF2, P16, and RASSF1A, which have Establishment and molecular characterization of cell lines from Japanese patients with malignant pleural mesothelioma KEN been reported to be frequently altered in MPM, were characterized (5)(6)(7). In addition, the status of the microRNA (miR) 34 family, which we have previously reported to be important in the pathogenesis of MPM, were analyzed (8).…”
Section: Introductionmentioning
confidence: 99%